2016
DOI: 10.2174/1381612822666160127114237
|View full text |Cite
|
Sign up to set email alerts
|

Cholinergic Targets in Lung Cancer

Abstract: Background Lung cancers express an autocrine cholinergic loop in which secreted acetylcholine can stimulate tumor growth through both nicotinic and muscarinic receptors. Because activation of mAChR and nAChR stimulates growth; tumor growth can be stimulated by both locally synthesized acetylcholine as well as acetylcholine from distal sources and from nicotine in the high percentage of lung cancer patients who are smokers. The stimulation of lung cancer growth by cholinergic agonists offers many potential new … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
65
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(73 citation statements)
references
References 73 publications
1
65
0
1
Order By: Relevance
“…In these cancers, ACh acts as an autocrine or local paracrine growth factor that stimulates tumor growth, with muscarinic cholinergic receptor subtype M3 or nicotinic cholinergic receptors functioning as its receptors (147, 149, 150), which is indicated in Figure 6. However, the free choline transported into some cells for this non-neuronal ACh synthesis is not dependent on CHT1 transport (150152). Knockdown of CTL4, but not other genes in the CTL family, in both lung and colon cancer cells significantly decreased ACh secretion and cell growth, suggesting that CTL4 is a reasonable target for certain types of cancer therapy without affecting neuronal ACh synthesis (150, 153).…”
Section: Choline Transportersmentioning
confidence: 99%
“…In these cancers, ACh acts as an autocrine or local paracrine growth factor that stimulates tumor growth, with muscarinic cholinergic receptor subtype M3 or nicotinic cholinergic receptors functioning as its receptors (147, 149, 150), which is indicated in Figure 6. However, the free choline transported into some cells for this non-neuronal ACh synthesis is not dependent on CHT1 transport (150152). Knockdown of CTL4, but not other genes in the CTL family, in both lung and colon cancer cells significantly decreased ACh secretion and cell growth, suggesting that CTL4 is a reasonable target for certain types of cancer therapy without affecting neuronal ACh synthesis (150, 153).…”
Section: Choline Transportersmentioning
confidence: 99%
“…It was originally believed that nAChRs are only present in the nervous system, but it has now been shown that they are expressed in numerous cell types. In particular, they are expressed in airway epithelial cells, which synthesize, store, process and secrete ACh (reviewed in Wessler and Kirkpatrick, ; Spindel, ). When lung cancer arises from airway epithelial cells, they continue to express nAChRs, and their growth is stimulated by nicotine (reviewed in Tournier and Birembaut, ).…”
Section: Introductionmentioning
confidence: 99%
“…Many studies recently have revealed that ACh also plays a non-neuronal role in some physiological and pathological process including inflammatory diseases89, functional bowel disorders1011, as well as several kinds of cancer1213. Several reports have indicated that ACh could act as a potential growth factor to stimulate cancer cell proliferation in lung cancer14, breast cancer15, colon cancer16 et al . Furthermore, ACh could also be synthesized and considered as auto-stimulating growth factor in some types of cancer1718.…”
mentioning
confidence: 99%